A dendrochronological investigation of Pinus radiata from Silvermine Nature Reserve - Midgley, John Claude (Department of Biological Sciences, 2017)
Whole trunk cross sections of Pinus radiata were collected from Silvermine Nature Reserve, Cape Town. The site was located on a hill in the nature reserve where precipitation was assumed to be a limiting factor in tree growth. Ring widths along 82 radii on 41 samples were measured to the closest 0.1 mm. Samples displaying the highest correlation between ring width values were selected to create a growth index chronology for the site. The resulting chronology was compared to various aspects of precipitation and temperature. Correlation coefficients between tree growth and annual, winter and growth season precipitation levels, minimum and maximum growth season temperatures, mean summer and mean winter temperatures were calculated with the use of a regression analysis. None of the correlation coefficients were above 0.1 , leading to the conclusion that the growth of trees was possibly disturbed by humans while the stand was under Cape Nature Conservation management. An alternative explanation could be that the height at which trees were sampled is likely to cause lowered correlation between samples as proposed by Fletcher (1974b). Although it is not statistically significant, trees displayed similar patterns to precipitation levels since 1955. The conclusion of this study is that Pinus radiata could provide a useful proxy record of climate in South Africa, but an undisturbed site where trees are limited by precipitation needs to be located before attempting the development of another ring index chronology.